1990
DOI: 10.1002/jcb.240430405
|View full text |Cite
|
Sign up to set email alerts
|

Growth and protein phosphorylation in the Nb2 lymphoma: Effect of prolactin, cAMP, and agents that activate adenylate cyclase

Abstract: The Nb2 T lymphoma is unique in that these lymphocytes proliferate in response to prolactin as well as in response to interleukin-2. In this study, we have examined the responsiveness of the adenylate cyclase system in Nb2 cells and the role of this signaling system in regulating proliferation and protein phosphorylation. An analog of cAMP inhibited prolactin-stimulated proliferation and blocked a prolactin-induced decrease in protein phosphorylation. Forskolin, a potent activator of adenylate cyclase in T lym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1992
1992
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Earlier studies have suggested that an adenylyl cyclase mediated accumulation of intracellular cAMP is the cause of adenosine‐induced cytotoxicity 67–70. In contrast, the viability of DU‐145, PC3, and LNcap prostate cancer cells was not affected by the activation of adenylyl cyclase by forskolin or by the addition of RO‐17721 (as phosphodiestrase inhibitor that increase cAMP).…”
Section: Discussionmentioning
confidence: 97%
“…Earlier studies have suggested that an adenylyl cyclase mediated accumulation of intracellular cAMP is the cause of adenosine‐induced cytotoxicity 67–70. In contrast, the viability of DU‐145, PC3, and LNcap prostate cancer cells was not affected by the activation of adenylyl cyclase by forskolin or by the addition of RO‐17721 (as phosphodiestrase inhibitor that increase cAMP).…”
Section: Discussionmentioning
confidence: 97%